Evaluation of the effect of different experimental and commercial natural extracts in the form of toothpastes and oral mouthrinses on the viability and activity of microcosm biofilm and on enamel demineralization prevention in vitro - Braga, Aline Silva (2022)
This thesis reports 4 manuscripts with the aim of evaluating the antibiofilm and anticaries effects of experimental or/and commercial solutions and toothpastes containing natural/herbal agents using a biofilm microcosm model on enamel. The 1st study evaluated the effects of commercial mouth rinses and toothpastes on bacteria viability, extracellular polysaccharide production (EPS) production and enamel demineralization by TMR. The 2nd study evaluated the effects of experimental and commercial mouth rinses on viability, lactic acid production, the CFU counting for cariogenic bacteria and demineralization by TMR. The 3rd and 4th reported the results of the effects of experimental or/and commercial mouth rinses and toothpastes containing natural extracts agents in high concentration on medium pH changes, viability of cariogenic bacteria by PCR and demineralization by OCT/TMR. Microcosm biofilm was produced on bovine enamel from pooled human saliva mixed with McBain saliva, under 0.2% sucrose exposure, for 5 days. The treatments were applied once (mouthrinse) or twice (toothpaste) a day (1 min or 2 min, respectively). Data were compared statistically by ANOVA/Tukey or Kruskal-Wallis/Dunn (p<0.05). The 1st study showed that 0.12% Chlorhexidine (CHX- PerioGard®) had significant effects on biofilm thickness, EPS, mineral loss and lesion depth, while Malva sylvestris (Malvatricin® Plus) significantly reduced mineral loss and lesion depth comparable to Chlorhexidine. Toothpaste containing propolis and Myrrh significantly reduced lesion depth, but only fluoride toothpaste (Colgate Total 12®) significantly reduced mineral loss. In the 2nd study, the lactic acid production was reduced by M. sylvestris (1.1 ± 0.2 g/L) and chlorhexidine (0.6 ± 0.2 g/L) compared to PBS (2.6 ± 1.3 g/L). Malva sylvestris, Matricaria chamomilla L. and chlorhexidine showed significant low CFU for Lactobacillus spp. and total streptococci. Only chlorhexidine significantly reduced S. mutans/S. sobrinus. Malva sylvestris (63.4% of mineral loss reduction), chlorhexidine (47.4%) and M. chamomilla L. (39.4%) significantly reduced enamel demineralization compared to PBS. By PCR, CHX eliminated Lactobacillus spp., as well as Malva sylvestris and CHX eliminated S. mutans, in agreement with the reduction of lesion depth and reflectivity (3rd study). The last study showed that, as far as assessable, Myrcia bella, Matricaria chamomilla, and Myrrha and propolis (commercial) toothpastes inhibited the outgrowth of S. mutans, while Lactobacillus spp. were reduced/eliminated by all toothpastes except Vochysia tucanorum. Mineral loss and lesion depth were significantly reduced by all toothpastes compared to the placebo. Malva sylvestris (as mouthrinse) and M. chamomilla (as mouthrinse and toothpaste) seems to be effective in controlling artificial enamel caries formation under this model.